PPW: uma tecnologia web de páginas dinâmicas baseada em Pascal - Werther Filho, João (2006)
Nowadays, the use of dynamic pages in development of web applications is, certainly, the most popular solution of the market and largely disseminated among the web developers, thanks to your edition, implementation and debug easiness. However, due to the interpretation of the code inside of scriptlets during your execution, they lose some performance, since the dynamic page is, in general, interpreted every time that is called. The use of a CGI (Common Gateway Interface) environment, that it runs executable files, working theoretically faster than interpreted pages, it would win in performance, but it would lose in development easiness offered by dynamic pages. To conjugate this easiness with a good performance, the solution for construction and processing of applications web would be the use of a development environment using dynamic pages, however with CGI execution environment. And it is exactly that what it intend to offer through the technology PPW (Pascal Pages for Web). The technology PPW conjugates a free environment of web applications development, using HTML dynamics pages, with an execution environment based on processing server-side CGI. It seeks to be available the same development easiness of other technologies based on dynamic pages, like ASP, PHP or JSP, associated to the good speed of executable of CGI applications. And all of this, using Pascal as pattern language.